Architecture in a climate of change : a guide to sustainable design - Smith, Peter F. (Peter Frederick), 1930- (Elsevier/Architectural Press, 2005)
Revised to incorporate and reflect changes and advances since it was first published the new edition of Architecture in a Climate of Change provides the latest basic principals of sustainability and the future of sustainable technology. Including new material on wind generation, domestic water conservation, solar thermal electricity as well as international case studies Architecture in a Climate of Change encourages readers to consider new approaches to building making minimum demand on fossil based energy.